Drawn to natural history: Enhancing field courses with drawing and field journal instruction. Issue 1 (10th August 2020) - Merkle, Bethann Garramon; Barber, Brian R.; Carling, Matthew D.
Abstract: Drawing is a long‐standing tool in the natural sciences, but training in this skill set has lapsed. We describe the impacts of field sketching instruction on the teaching practices of faculty and the experiences of students in two sections of a freshman‐level course on natural history. We examine self‐reported data from participating faculty and students. We focus on their perspectives of drawing and natural history practices before and after drawing training and a field journal requirement. Faculty reported positive shifts in their views of the value and feasibility of incorporating drawing in their courses. We observed positive shifts in students' attitudes about drawing and appreciation of nature, as indicated by students' field journal entries and survey responses. Given the sample size ( n = 26 students, n = 2 faculty), our ability to draw inference is constrained. Thus, we present these results to provide context for the overall process of efforts to integrate drawing more fully into natural science courses. For university instructors interested in incorporating drawing into their natural science courses, we also provide advice rooted in the literature and best practices of art‐science integration. Our results suggest that on‐going, artist‐facilitated training for faculty and students can enhance the experience of using drawing in natural history courses and reconnect natural scientists at all career levels to drawing as a valuable, professional tool.